Range‐wide indicators of African great ape density distribution. Issue 12 (18th October 2021) - Ordaz‐Németh, Isabel; Sop, Tenekwetche; Amarasekaran, Bala; Bachmann, Mona; Boesch, Christophe; Brncic, Terry; Caillaud, Damien; Campbell, Geneviève; Carvalho, Joana; Chancellor, Rebecca; Davenport, Tim R. B.; Dowd, Dervla; et al.
Abstract: Species distributions are influenced by processes occurring at multiple spatial scales. It is therefore insufficient to model species distribution at a single geographic scale, as this does not provide the necessary understanding of determining factors. Instead, multiple approaches are needed, each differing in spatial extent, grain, and research objective. Here, we present the first attempt to model continent‐wide great ape density distribution. We used site‐level estimates of African great ape abundance to (1) identify socioeconomic and environmental factors that drive densities at the continental scale, and (2) predict range‐wide great ape density. We collated great ape abundance estimates from 156 sites and defined 134 pseudo‐absence sites to represent additional absence locations. The latter were based on locations of unsuitable environmental conditions for great apes, and on existing literature. We compiled seven socioeconomic and environmental covariate layers and fitted a generalized linear model to investigate their influence on great ape abundance. We used an Akaike‐weighted average of full and subset models to predict the range‐wide density distribution of African great apes for the year 2015. Great ape densities were lowest where there were high Human Footprint and Gross Domestic Product values; the highest predicted densities were in Central Africa, and the lowest in West Africa. Only 10.7% of the total predicted population was found in the International Union for Conservation of Nature Category I and II protected areas. For 16 out of 20 countries, our estimated abundances were largely in line with those from previous studies. For four countries, Central African Republic, Democratic Republic of the Congo, Liberia, and South Sudan, the estimated populations were excessively high. We propose further improvements to the model to overcome survey and predictor data limitations, which would enable a temporally dynamic approach for monitoring great apes across their range based on key indicators. Abstract : Human Footprint and Gross Domestic Product are important indicators for African great ape density. Highlights: We identified the Human Footprint and Gross Domestic Product as important indicators predicting African great ape density at the continental scale. Using site‐level abundance data, we predicted density and distribution for African great apes across their entire range.